2019
DOI: 10.1111/pops.12572
|View full text |Cite
|
Sign up to set email alerts
|

Global Human Identification and Citizenship: A Review of Psychological Studies

Abstract: We review psychological research on global human identification and citizenship, Thomas Paine's belief that "The world is my country, and all mankind are my brethren." In turn, we review the theoretical foundations that guided our work, research with measures that preceded our own, and our own work with our correlated scales. We review its foundations, its effects upon attitudes and behaviors, and how it might be enlarged. Global human identification and citizenship is related negatively to ethnocentrism, auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
201
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(219 citation statements)
references
References 129 publications
11
201
1
6
Order By: Relevance
“…Regional and national place attachment did not relate with policy support although it was operationalized on different geographical levels. This is in line with previous literature finding global identity – a concept closely related to global place attachment – to be an important predictor for pro-environmental behavior and policy support ( Rosenmann et al, 2016 ; Joanes, 2019 ; Loy and Reese, 2019 ; for an overview, see McFarland et al, 2019 ).…”
Section: Study 2: Correlational Studysupporting
confidence: 92%
“…Regional and national place attachment did not relate with policy support although it was operationalized on different geographical levels. This is in line with previous literature finding global identity – a concept closely related to global place attachment – to be an important predictor for pro-environmental behavior and policy support ( Rosenmann et al, 2016 ; Joanes, 2019 ; Loy and Reese, 2019 ; for an overview, see McFarland et al, 2019 ).…”
Section: Study 2: Correlational Studysupporting
confidence: 92%
“…In particular, while our findings support the statement that identification with humanity and global citizenship partly share a common meaning (McFarland et al, 2019), they also provide evidence to the claim that they might be better represented as separate constructs.…”
Section: Discussionsupporting
confidence: 81%
“…In general, research has yielded mixed findings regarding the effects of all-inclusive identities. Some studies revealed positive responses from high identifiers with humans and with all humanity, such as less hostility toward asylum seekers (Nickerson & Louis, 2008), less threat towards religious groups (Dunwoody & McFarland, 2018), less dehumanization towards minority groups (Albarello & Rubini, 2012;Hamer, McFarland, & Drogosz, in prep., as cited in McFarland et al, 2019), less ethnocentrism (McFarland et al, 2012, less collective narcissism (McFarland et al, 2019), more solidarity and collective action (Barth et al, 2015), more commitment to human rights (McFarland et al, 2012), and forgiveness of former national enemies (Hamer, Penczek, & Bilewicz, 2018). Likewise, high identifiers with the world population and with a global community, also revealed more intentions to act against global inequality (Reese et al, 2014), promotion of social justice and helping (Reysen & Katzarska-Miller, 2013), as well as social responsibility and global activism (Reysen & Hackett, 2017).…”
Section: Inclusive Social Identities and Intergroup Relationsmentioning
confidence: 94%
See 1 more Smart Citation
“…conceptually like cosmopolitanism. Both religiosity (Ysseldyk et al, 2010) and nationalism (Mummendey et al, 2001) can be understood as powerfully existing systems of power and identification that may offer resistance to cosmopolitanism (McFarland et al, 2019). But the exact relationship between them is still not well known.…”
mentioning
confidence: 99%